A new arc detection method based on fuzzy logic using S-transform for pantograph-catenary systems - Karakose, Ebru; Gencoglu, Muhsin Tunay; Karakose, Mehmet; Yaman, Orhan; Aydin, Ilhan; Akin, Erhan (Springer, 2018)
pantograph-catenary system is one of the critical components used in electrical trains. It ensures the transmission of the electrical energy to the train taken from the substation that is required for electrical trains. The condition monitoring and early diagnosis for pantograph-catenary systems are very important in terms of rail transport disruption. In this study, a new method is proposed for arc detection in the pantograph-catenary system based signal processing and S-transform. Arc detection and condition monitoring were achieved by using current signals received from a real pantograph-catenary system. Firstly, model based current data for pantograph-catenary system is obtained from Mayr arc model. The method with S-transform is developed by using this current data. Noises on the current signal are eliminated by applying a low pass filter to the current signal. The peak values of the noiseless signals are determined by taking absolute values of these signals in a certain frequency range. After the data of the peak points has been normalized, a new signal will be obtained by combining these points via a linear interpolation method. The frequency-time analysis was realized by applying S-transform on the signal obtained from peak values. Feature extraction that obtained by S-matrix was used in the fuzzy system. The current signal is detected the contdition as healthy or faulty by using the outputs of the fuzzy system. Furthermore the real-time processing of the proposed method is examined by applying to the current signal received from a locomotive.
Keywords: pantograph-catenary system; Arc detection; S-transform; Mayr arc model; Fuzzy system